MODERASI BERAGAMA DAN TANTANGAN DAKWAH ISLAM DI ERA DIGITAL: REKONSTRUKSI DALAM MULTIKULTURAL INDONESIA - Asrizal; Rahmat Hidayat; Novita, Sri (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2026)
Abstract. This article aims to explore the reconstruction of religious moderation (wasathiyyah) within the horizon of Islamic da’wah amidst the complexities of Indonesia's multicultural society. Utilizing a qualitative library research method, this study dissects how moderate values are produced and distributed in the digital age. The findings indicate that moderation is no longer merely a static theological doctrine but has evolved into a dynamic communicative strategy. In practice, digital da’wah is heavily influenced by media framing, where the construction and